Pengembangan Sistem Informasi Manajemen Siswa (Studi Kasus: SMA Negeri 9 Malang) - Muhammad Amir Razzak; Widhy Hayuhardhika Nugraha Putra; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
SMAN 9 Malang is one of the public schools owned by Malang City. Even though it is relatively new, SMAN 9 Malang always tries to implement various uses of IT in schools, such as in the multimedia-based study room and computer laboratory. Based on the results from the interviews conducted by the examiners with Wakahumas there, SMAN 9 Malang does not have a special information system used to manage student data there. The whole process of recording student data is still done manually. Whether it's attendance system, violation record, guidance record, and student achievement record is still done manually. Normally, the teacher takes data from the class manually, then gives it to the TU for further input into the Ms. Excel on the school's computer. This makes it just to see the data, you need to contact the TU or meet Wakahumas. In overcoming the problem above, a solution was made in the form of a student management information system that was built using the agile rapid prototyping method. At the analysis and design stage, a model is built that can be used as communication between researchers and stakeholders in order to find the best solution in system development. The models used at this stage include use case diagrams, use case scenarios, sequence diagrams, class diagrams, and physical data models. The system is developed using php with laravel framework for website and flutter for mobile. The system that has been built is tested using blackbox testing and user acceptance test (UAT). Blackbox testing showing valid in all tests and UAT testing scores 96.42% for teacher users and scores 87.60% for students users.